Single cell analysis reveals distinct immune landscapes in transplant and primary sarcomas that determine response or resistance to immunotherapy - Amy J. Wisdom (Nature Portfolio, 2020)
Promising results of cancer therapies in transplant tumor models often fail to predict efficacy in clinical trials. Here the authors show that, while transplant tumors are cured by radiotherapy and PD-1 blockade, autochthonous sarcomas are resistant to the identical treatment, recapitulating the immune landscape and resistance to checkpoint blockade observed in most sarcoma patients.